Resumption of Employment after Cervical Cancer Surgery: a 3-Year Follow-Up Study of Long-term Outcomes - Dmitry V. Blinov; Antonina G. Solopova; Elena V. Gameeva; Nazim G. Badalov; Mikhail A. Eremushkin; Alexandra M. Stepanova; Vsevolod N. Galkin; Alexander E. Ivanov; Saida A Akavova (Вестник восстановительной медицины)
INTRODUCTION. Despite advancements in cervical cancer (CC) diagnosis and treatment, surgical intervention remains the cornerstone of radical treatment. However, surgical procedures can result in complications such as lymphedema, sexual dysfunction, and other physical and psychosocial disorders, significantly affecting patients' quality of life (QoL) and ability to return to work. This emphasizes the need for effective strategies to support patients in resuming their occupational activities post-treatment.